2017
DOI: 10.1158/0008-5472.can-17-1375
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp miR-S8 Suppresses the Stemness of Human Melanoma Stem-like Cells by Targeting the Transcription Factor YB-1

Abstract: Cross-species regulation of gene expression by microRNA is a possible untapped opportunity for miRNA-based therapy. In this study, we report a novel approach to ablate melanoma stem-like cells by targeting the transcription factor YB-1, which is significantly and selectively upregulated in these cells in melanoma. Silencing YB-1 expression was sufficient to significantly inhibit the stemness of melanoma stem-like cells. In exploring YB-1 targeting, we discovered that the shrimp microRNA miR-S8 could suppress h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…When shrimp miR‐S8 was cotransfected with YB‐1 3′‐UTR plasmid, the luciferase activity was significantly decreased. It indicated that miR‐S8 suppresses the stemness of human melanoma stem‐like cells by targeting the transcription factor YB‐1 (F. Yang, Wei, Zhang, & Zhang, ). By regulating the expression of foxl3 by binding to foxl3 3′‐UTR wild‐type plasmid, mal‐miR‐9 was involved in promoting oocyte degeneration in the ovotestis, and stimulating spermatogenesis in spermatogonia in Monopterus albus (Y. Gao, Jia, Hu, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…When shrimp miR‐S8 was cotransfected with YB‐1 3′‐UTR plasmid, the luciferase activity was significantly decreased. It indicated that miR‐S8 suppresses the stemness of human melanoma stem‐like cells by targeting the transcription factor YB‐1 (F. Yang, Wei, Zhang, & Zhang, ). By regulating the expression of foxl3 by binding to foxl3 3′‐UTR wild‐type plasmid, mal‐miR‐9 was involved in promoting oocyte degeneration in the ovotestis, and stimulating spermatogenesis in spermatogonia in Monopterus albus (Y. Gao, Jia, Hu, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…Shrimp miRNA‐S8 inhibited the expression of the YB‐1 transcription factor in a cross‐species manner, targeting the 3′UTR of YB‐1 mRNA and mediating its degradation, leading to the suppression of tumorigenesis in melanoma cells (Yang et al . ). It has been suggested that antiviral miRNAs may have antitumour capacity because, in general terms, tumorigenesis results from a metabolic disorder of cells.…”
Section: Shrimp Micrornas With Antitumoral Activity: An Alternative Smentioning
confidence: 97%
“…Melanoma cell line MDA-MB-435 and breast cancer cell line MDA-MB-453 were purchased from American Type Culture Collection (Manassas, VA, USA). Melanoma stem cells and nonstem cells were sorted from MDA-MB-435 cells by our laboratory as previously described in Yang et al (24). Breast cancer stem cells and nonstem cells were sorted in the present study.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Cancer stem cells and the corresponding cancer nonstem cells were sorted from 2 types of cancer cells (MDA-MB-453 and MDA-MB-435). MDA-MB-435 stem cells were obtained in our previous study (24). For the sorting of stem cells from MDA-MB-453 cells, the ALDH1-positive cells were sorted as cancer stem cells (Fig.…”
Section: Aldh1-positive Mda-mb-453 Breast Cancer Cells Have Stem Cellmentioning
confidence: 99%
See 1 more Smart Citation